Parasitism of Adult Pentatomidae by Tachinidae in Soybean in the North Central Region of the United States. Issue 3 (4th May 2020) - Anderson, Pheylan A; Pezzini, Daniela T; Bueno, Nádia M; DiFonzo, Christina D; Finke, Deborah L; Hunt, Thomas E; Knodel, Janet J; Krupke, Christian H; McCornack, Brian P; Philips, Christopher R; Varenhorst, Adam J; Wright, Robert J; et al.
Abstract: Stink bugs (Hemiptera: Pentatomidae) are agricultural pests of increasing significance in the North Central Region of the United States, posing a threat to major crops such as soybean. Biological control can reduce the need for insecticides to manage these pests, but the parasitism of stink bugs by Tachinidae (Diptera) is poorly characterized in this region. The objective of this study was to evaluate the rate of parasitism of stink bugs by tachinids over 2 yr from nine states across the North Central Region. Parasitism was assessed by quantifying tachinid eggs on the integument of stink bug adults. Parasitism rates (i.e., percent of adult stink bugs with tachinid eggs) were compared across stink bug species, states, stink bug sex, and years. The mean percent parasitism of stink bugs by tachinids was about 6% across the region and did not differ among stink bug species. Mean percent parasitism was significantly higher in Missouri than in northern and western states. In addition, male stink bugs had significantly higher mean percent parasitism than females. Stink bug species commonly found in soybean in the region showed some parasitism and are therefore potentially vulnerable to oviposition by these parasitoids. This is the first study to characterize the level of parasitism of stink bugs by tachinids across the North Central Region.